Deer remains from the Middle Pleistocene site of Gruta da Aroeira (Portugal): Iberian faunal endemism and implications for hominin paleobiogeography. (1st December 2019) - Croitor, Roman; Sanz, Montserrat; Daura, Joan
Abstract: The article presents a description of cervid remains from the Middle Pleistocene Acheulean site of Gruta da Aroeira (= Galerias Pesadas) in central Portugal. The assemblage comprises the remains of four deer species: Cervus elaphus, Praedama cf . savini, Haploidoceros mediterraneus, and Dama cf. vallonnetensis, making Gruta da Aroeira the first site in the Iberian Peninsula at which the genus Haploidoceros has been documented in the Middle Pleistocene. Virtually all the cervids documented at the site demonstrate a degree of endemism, including evolutionary modifications of skull, antlers and dentition or a reduction in body size. The unusual richness of the cervid community at Gruta da Aroeira may be related to the specific biogeographic conditions of the Middle Pleistocene in Iberia. Thus, while the Iberian Peninsula's geographical link with the temperate west Eurasian zone facilitated the dispersal of cervids of palearctic origin into Iberia, it impeded the dispersal of ruminants from warmer, more arid areas. The endemic character of the Middle Pleistocene cervids and the biodiversity of the Iberian Peninsula should shed some light on the paleobiogeography of Iberian hominins and their role in hominin hunting or their economic strategies. Highlights: The Middle Pleistocene paleoathropological site of Gruta da Aroeira (Portugal) have yielded tremains of four cervid species . Most of Middle Pleistocene Iberian cervid lineages are characterized by a certain degree of endemism . Dama cf. vallonnetensis and a small form of Praedama are archaic elements of the Gruta da Aroeira fauna. Iberian Pleistocene assemblages of ruminants are ecologically different from African ruminant assemblages. Acheulian technological innovations spread across the European continent regardless of paleobiogeographic boundaries.